Create the perfect fit : measuring and pattern fitting for real sewing solutions - Mahon, Joi (Fons & Porter, 2014)
"Joi will guide you through evaluating the body, compensating for figure variations, taking extensive measurements and applying them to a commercial pattern to see how these vital pattern adjustments affect fit."--Provided by publisher.